Real Exchange Rate Misalignment and Economic Growth Nexus: Evidence from Southern African countries - Eugine Tafadzwa Maziriri; Knowledge Mutodi; Tinashe Chuchu (KINERJA, 2021)
This paper investigates the link between real exchange rate misalignment and Southern African countries' economic growth. The study used panel data for 16 Southern African countries over 17 years. Generalized methods of moments (GMM) was applied to analyze the panel growth equation. The estimated results have suggested that the real exchange rate, real exchange rate misalignment, terms of trade, and foreign direct investment explains variation in income growth of southern African countries. The real exchange rate appreciation over the study period has adversely affected growth, whereas real exchange rate undervaluation suggests a positive impact on annual income growth. Unfavourable terms of trade were found to hurt growth, whereas foreign direct investment upsurge stimulates growth. Thus, policymakers in their respective African countries ought to diligently monitor real exchange rate misalignment in the foreign exchange market. An increase in real exchange rate overvaluation may adversely affect the trade and current account balances, which might ultimately hurt growth.